DEVELOPMENT OF E-MODULE INTEGRATED STEM-BASED INQUIRY LEARNING IN VOCATIONAL PHYSICS STUDIES - Halimatus Sakdiah; Nanda Novita; Muliani Muliani (Jurnal Pendidikan Fisika, 2020)
During the current pandemic, learning vocational physics studies courses are carried out online but there is not yet adequate media. So it is considered necessary to develop teaching materials in the form of e-modules to support the learning process. Development research e-module integrated STEM based inquiry learning in vocational physics studies courses aims to see the feasibility of e-modules on material expert assessments and media expert assessments as well as student readability of e-modules. This research uses design ADDIE (Analysis, Design, Development, Implementation, Evaluation) and implemented in the UNIMAL Physics Education Study Program. The results of this research are: (1) the validation on the aspect of the evaluation of material experts is worth 74.27% with a fairly valid category with a reliability of 86.31% in the very good category, (2) the validation on the aspect of the assessment of the media expert is worth 77.8% with the category very valid, or can be used without revision with a reliability value of  98.34% with a very good category and (3) a student response value of 85.09%, with very attractive criteria. So it can be concluded that the STEM-based e-module integrated inquiry learning in vocational physics studies courses is declared feasible to use.